Data analysis of simulated WoT-based anti-crime scenario. (11th March 2021) - Kuang, Chih-Chi; Wang, Kuei Min; Hui, Lin; Chang, Chuan-Yu; Chiu, Kuang Hui
This study proposes a novel WoT concept for improving the current police work on anti-terrorist. In order to prove the feasibility and effectiveness, the presented WoT-based police rescue squad force (RSF) concept is modelled and simulated by a Monte Carlo simulation. The current RSF and WoT-based are two alternatives that are analysed for the comparison. The simulation results show that a significant difference between the current RSF and WoT-based exists. The information gained from the simulation reveals the WoT-based RSF can support the commander's decision makers in performing the anti-terrorist task with less risk, less cost with high effectiveness. This study makes an exceedingly contribution which the WoT-based RSF concept is viable and can easily improve police performance in anti-terrorist and hostage rescue tasks.